Engineering collagenous analogs of connective tissue extracellular matrix - Brudnicki, Philip A. P.; Gonsalves, Matthew A.; Spinella, Stephen M.; Kaufman, Laura J.; Lu, Helen H. (Frontiers in Bioengineering and Biotechnology, 2022)
Connective tissue extracellular matrix (ECM) consists of an interwoven network of contiguous collagen fibers that inform cell activity, direct biological function, and guide tissue homeostasis throughout life. Recently, ECM analogs have emerged as a unique ex vivo culture platform for studying healthy and diseased tissues and in the latter, enabling the screening for and development of therapeutic regimen. Since these tissue models can mitigate the concern that observations from animal models do not always translate clinically, the design and production of a collagenous ECM analogue with relevant chemistry and nano- to micro-scale architecture remains a frontier challenge in the field. Therefore, the objectives of this study are two-fold— first, to apply green electrospinning approaches to the fabrication of an ECM analog with nanoscale mimicry and second, to systematically optimize collagen crosslinking in order to produce a stable, collagen-like substrate with continuous fibrous architecture that supports human cell culture and phenotypic expression. Specifically, the “green” electrospinning solvent acetic acid was evaluated for biofabrication of gelatin-based meshes, followed by the optimization of glutaraldehyde (GTA) crosslinking under controlled ambient conditions. These efforts led to the production of a collagen-like mesh with nano- and micro-scale cues, fibrous continuity with little batch-to-batch variability, and proven stability in both dry and wet conditions. Moreover, the as-fabricated mesh architecture and native chemistry were preserved with augmented mechanical properties. These meshes supported the in vitro expansion of stem cells and the production of a mineralized matrix by human osteoblast-like cells. Collectively these findings demonstrate the potential of green fabrication in the production of a collagen-like ECM analog with physiological relevance. Future studies will explore the potential of this high-fidelity platform for elucidating cell-matrix interactions and their relevance in connective tissue healing.